If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (2x + -3)(7 + -1x) Reorder the terms: y = (-3 + 2x)(7 + -1x) Multiply (-3 + 2x) * (7 + -1x) y = (-3(7 + -1x) + 2x * (7 + -1x)) y = ((7 * -3 + -1x * -3) + 2x * (7 + -1x)) y = ((-21 + 3x) + 2x * (7 + -1x)) y = (-21 + 3x + (7 * 2x + -1x * 2x)) y = (-21 + 3x + (14x + -2x2)) Combine like terms: 3x + 14x = 17x y = (-21 + 17x + -2x2) Solving y = -21 + 17x + -2x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -21 + 17x + -2x2
| 12-6(5x-8)-9x=-2(-8x+7)-10 | | 15+45x=240 | | (c+4)(c-7)=0 | | 6x-10=8x-24 | | 3X+2+38=7X | | 12x-4=-32 | | 6x+9y=-27 | | x^6-7x^3= | | 6q-3p=p+q | | y/8=y/5-4/5 | | 6=-5x+7 | | 3x+-y=22 | | 2x+20-y= | | x^8-y^8= | | 34-y=y+6 | | 129x^4+33ax^2+9a= | | x^(7/2)=51,4 | | 3(6+5x)=18 | | -3(3p+2)-2(5-8p)=3(7+2p) | | 4x-(-3)(-2)=18 | | 4x-16=3x-1.9 | | 4x(-3)(-2)=18 | | 2(6+x)=32 | | -12h-2(2h-6)=-36 | | 3y^4+6y^3+3y^2=0 | | c-62=812 | | 5xy-10x= | | 9x^4+9x^3y-x^2-xy= | | 7m=147 | | 11-(k+3k)=43 | | 1/3,1/4,1/5,1/6= | | 2y-1/3=x |